Tumor macrophages are pivotal constructors of tumor collagenous matrix - Afik, Ran; Zigmond, Ehud; Vugman, Milena; Klepfish, Mordehay; Shimshoni, Elee; Pasmanik-Chor, Metsada; Shenoy, Anjana; Bassat, Elad; Halpern, Zamir; Geiger, Tamar; Sagi, Irit; Varol, Chen (The Journal of experimental medicine, 2016)
Tumor-associated macrophages (TAMs) promote tumor development, invasion, and dissemination by various mechanisms. In this study, using an orthotopic colorectal cancer (CRC) model, we found that monocyte-derived TAMs advance tumor development by the remodeling of its extracellular matrix (ECM) composition and structure. Unbiased transcriptomic and proteomic analyses of (a) TAM-abundant and -deficient tumor tissues and (b) sorted tumor-associated and -resident colonic macrophage subpopulations defined a distinct TAM-induced ECM molecular signature composed of an ensemble of matricellular proteins and remodeling enzymes they provide to the tumor microenvironment. Remarkably, many of these ECM proteins are specifically increased in human CRC versus healthy colon. Specifically, we demonstrate that although differentiating into TAMs, monocytes up-regulate matrix-remodeling programs associated with the synthesis and assembly of collagenous ECM, specifically collagen types I, VI, and XIV. This finding was further established by advanced imaging showing that TAMs instruct the deposition, cross-linking, and linearization of collagen fibers during tumor development, especially at areas of tumor invasiveness. Finally, we show that cancer-associated fibroblasts are significantly outnumbered by TAMs in this model and that their expression of collagen XIV and I is reduced by TAM deficiency. Here, we outline a novel TAM protumoral function associated with building of the collagenous ECM niche.